2017
DOI: 10.1038/npp.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Microglial Activation in Individuals at Clinical High Risk for Psychosis: an In Vivo PET Study with [18F]FEPPA

Abstract: Several lines of evidence implicate microglial activation and abnormal immune response in the etiology of psychosis. Previous positron emission tomography (PET) neuroimaging studies of the translocator protein 18 kDa, TSPO, were limited by low affinity of the first-generation radioligand, low-resolution scanners, and small sample sizes. Moreover, there is a dearth of literature on microglial activation in individuals at clinical high risk (CHR) for psychosis. We used a novel second-generation TSPO radioligand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 46 publications
(72 reference statements)
4
40
0
Order By: Relevance
“…We found no significant group effect on [ 18 F]FEPPA V T which is in line with five previous studies that examined TSPO expression in psychosis using second generation TSPO radioligands and V T as outcome measure 912, 14, 20 and also two other studies that used [ 11 C]PK11195 13, 15 . A recent study, however, reported a significantly lower TSPO expression in first-episode psychosis as compared to healthy volunteer using [ 11 C]PBR28 16 .…”
Section: Discussionsupporting
confidence: 91%
“…We found no significant group effect on [ 18 F]FEPPA V T which is in line with five previous studies that examined TSPO expression in psychosis using second generation TSPO radioligands and V T as outcome measure 912, 14, 20 and also two other studies that used [ 11 C]PK11195 13, 15 . A recent study, however, reported a significantly lower TSPO expression in first-episode psychosis as compared to healthy volunteer using [ 11 C]PBR28 16 .…”
Section: Discussionsupporting
confidence: 91%
“…Out of the studies included in this meta-analysis, one reported a significant elevation of DVR in schizophrenia patients and people at clinical risk for psychosis (22) whereas three studies showed no difference in schizophrenia (23)(24)(25). More recently, no increase in DVR was found in high risk individuals (67). We chose not to include DVR in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the findings of an increased uptake of this tracer in these pathologies, limitations including low signalto-noise ratio and high non-specific binding has addressed for the synthesis of second-and third-generation TSPO-specific radiopharmaceuticals, linked to [ 11 C] or [ 18 F] and including (Luo et al, 2018;Singhal et al, 2018;Best et al, 2019). Similarly, different studies have reported selective microglial uptake of these tracers in multiple sclerosis animal models and patients (Hagens et al, 2018;Herranz et al, 2019;Nack et al, 2019), amyotrophic lateral sclerosis (Zürcher et al, 2015;Datta et al, 2017), Alzheimer's disease (Alam et al, 2017;Keller et al, 2018;Focke et al, 2019), and Lyme disease on humans (Coughlin et al, 2018), and stroke experimental models (Miyajima et al, 2018), with more discordant results for psychiatric patients, suffering from schizophrenia (Di Biase et al, 2017;Hafizi et al, 2017;Ottoy et al, 2018;Selvaraj et al, 2018) and major depression (Li et al, 2018), probably due to the different stage of disease. Interestingly, one study on fibromyalgia subjects attempts to demonstrate specificity of TSPO tracers for microglia, considering that an high expression of this molecule was also detected in activated astrocytes (Albrecht et al, 2019).…”
Section: Pet and Mr Imaging Of Microglial Activationmentioning
confidence: 99%
“…The authors, using [ 11 C]PBR28, which binds to the TSPO, and [ 11 C]-DED thought to primarily reflect astrocytic (but not microglial) signal, demonstrated although in a small size sample, a selective cortical uptake of microglial tracer but not of the astrocytic one (Albrecht et al, 2019). Nevertheless, the application of TSPO tracers is affected by significant inter-subjects variability, essentially due to a rs6971 polymorphism that affects TSPO binding mainly in firstand second-generation radioligands (Hafizi et al, 2017), and more importantly, they are not able to differentiate microglial phenotype, distinguishing between conservative and detrimental activation. Moreover, although TSPO is upregulated in activated glial cells, its function and role in the immunity response is still unclear.…”
Section: Pet and Mr Imaging Of Microglial Activationmentioning
confidence: 99%